THE CONCEPT OF ENTERPRISE COMPETITION IN THE CONTEXT OF MODERNIZATION AND ITS ESSENCE - Abdiev Behzod Kuvvatalievich (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
This article presents ideas and opinions about the concept of enterprise competition and its essence in the context of modernization.